GI-POF Transmission At Different Bit Rates, Fiber Lengths and Wavelengths: 1310 and 1550 Nm - Hossam Selmy; Gil Fernandes; Rogerio Nogueira; Ricardo Oliveira (IEEE Photonics Journal, 2024)
The paper demonstrates the transmission of variable bit rates NRZ streams over different lengths of perfluorinated graded-index plastic optical fiber GI-POF at wavelengths of 1550 and 1310 nm. Specifically, at $λ$ = 1550 nm, 16, 14 and 12 Gbps of NRZ transmissions are demonstrated for 50 m GI-POF. Furthermore, at $λ$ = 1310 nm, 10 and 8 Gbps NRZ transmissions are demonstrated for distances of 50, 100 and 200 m. The performance is evaluated for realized transmissions in terms of received bit-error rate versus transmitted optical power and is compared to back to back performance.